Interstate Water Compacts : Intergovernmental Efforts to Manage America's Water Resources - Zimmerman, Joseph Francis, 1928- (Book collections on Project MUSE., 2012)
"This groundbreaking work is the first to devote itself to interstate and federal-interstate compacts pertaining to controversies including the abatement of water pollution, apportionment of river waters, economic development, flood control, inland fisheries, marine fisheries, and restoration to rivers of anadromous fish such as salmon and shad. The process for entering into interstate and federal-interstate compacts is explained in detail, as is the exercise of original jurisdiction by the US Supreme Court to resolve intractable interstate controversies involving interpretation of provisions of compact, water apportionment, and water pollution abatement"--Provided by publisher.